2015
DOI: 10.1097/jnn.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profiles of Cerebral Perfusion Pressure After Subarachnoid Hemorrhage

Abstract: Introduction Insufficient cerebral perfusion pressure (CPP) after aneurysmal subarachnoid hemorrhage (aSAH) can impair cerebral blood flow (CBF). We examined the temporal profiles of CPP change and tested whether these profiles were associated with delayed cerebral ischemia (DCI). Method CPP values were retrospectively reviewed for 238 subjects. Intracranial pressure and mean arterial pressure values were obtained every 2 hours for 14 days. Induced hypertension was utilized to prevent vasospasm. The linear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Patients with high ADL score, their autonomy is higher, and corresponding SS-QOL level can be improved. Some other studies showed that, 13,14 CNP can improve the GCS score of patients with cerebral hemorrhage, improve their GOS score and cognitive function, and lower the incidence of POCD.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with high ADL score, their autonomy is higher, and corresponding SS-QOL level can be improved. Some other studies showed that, 13,14 CNP can improve the GCS score of patients with cerebral hemorrhage, improve their GOS score and cognitive function, and lower the incidence of POCD.…”
Section: Discussionmentioning
confidence: 96%
“…Because aneurysm rupture is usually combined with IPH or IVH and SDH, intracranial pressure of such patients is relatively higher compared to patients with simple SAH. Moreover, some patients may lose treatment opportunity due to deteriorated condition caused by sharp increase in intracranial pressure, and therefore, their prognosis may become much worse compared to patients with simple SAH [ 2 , 3 ]. The patient in this study had hematoma in the left temporal lobe without SAH, which was confirmed by head CT scan at the time of admission.…”
Section: Discussionmentioning
confidence: 99%